2014
DOI: 10.11648/j.ijmsa.20140303.17
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Influence of the Tempering on Electric Properties Films Bi2Te3

Abstract: Abstract:Processes of oxidation in the films Bi 2 Te 3 used in the various thermoelectric film devices working on air at various temperatures are investigated. Samples Bi 2 Te 3 of p-type thickness received 0,5-1,5 microns a method of discrete evaporation with additional homogenization of a steam phase. Changing technological conditions to raise dust and tempering, have received samples with a wide set of concentration of carriers of a charge from 5х10 18 up to 6х10 19 cm -3 . The fact of formation oxide layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The existence of a Schottky barrier or a rectifying barrier of a different type at the back contact is confirmed by the experiments on inducing an electron beam in the current elements in the presence of a bias voltage. According to measurements of the induced current during illumination of elements using an additional radiation source, there is no light-induced barrier, although several research groups have suggested its existence [8][9][10][11].…”
Section: Methodsmentioning
confidence: 99%
“…The existence of a Schottky barrier or a rectifying barrier of a different type at the back contact is confirmed by the experiments on inducing an electron beam in the current elements in the presence of a bias voltage. According to measurements of the induced current during illumination of elements using an additional radiation source, there is no light-induced barrier, although several research groups have suggested its existence [8][9][10][11].…”
Section: Methodsmentioning
confidence: 99%